KECEMASAN AKADEMIK SERTA DAMPAKNYA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI: STUDI TENTANG PENGALAMAN PESERTA DIDIK DI SMAN 5 KARAWANG - Syifa, Rumaita; Debibik Nabilatul Fauziah; Neng Ulya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mental health is an important aspect of education because it affects students' ability to participate optimally in the learning process. One of the mental health problems often found in schools is academic anxiety, a psychological condition marked by worry, fear of failure, fear of making mistakes, and low self-confidence in facing academic demands. This study aims to describe students' experiences of academic anxiety, its impact on Islamic Religious Education and Character Education learning, the factors that influence it, and the efforts made by teachers and the school environment to help students manage academic anxiety at SMAN 5 Karawang. This research used a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the Miles, Huberman, and Saldana model, including data reduction, data display, and conclusion drawing. The findings show that students experience anxiety in the form of fear of answering incorrectly, nervousness when performing in front of the class, worry about memorization and evaluation, and low self-confidence. Academic anxiety decreases concentration, lowers classroom participation, reduces self-confidence, and makes learning outcomes less optimal. Active learning, motivation, personal approaches, and a supportive learning environment help students manage anxiety during learning.